The allergic reaction - Rihoux, Jean-Pierre (Braine-l'Alleud : UCB Pharmaceutical Sector, 1993)
The purpose of this book is to present an exhaustive summary of the latest concepts relating to a whole group of diseases covered by the term "allergy" or "atopic state". Such conditions are generally acknowledged to be on the increase. In Scandinavia, for example, over 10% of the population as a whole suffers from allergies to various pollens. This book therefore addresses itself to a major issue of public health. In addition it deals with some fascinating problems of biology and medicine, since the subject of the book is one where a number of different disciplines overlap; but what it does also is to place at last on a proper scientific footing such nebulous concepts as "reactivity", "allergy" and "atopic conditions".
Obsahuje bibliografie
Keywords: hypersenzitivita; hypersenzitivita včasná; farmakoterapia; príručka